Research on the Design of Experiential Renovation of Rural Residential Buildings in Inner Mongolia - Kong, Fanguang; Fang , Hongwei (Pacific International Journal, 2023)
This research explores the experiential renovation design for rural residential buildings in Inner Mongolia, aiming to revitalize rural areas and develop the tourism industry while preserving traditional culture. It incorporates literature review, field study, and case analysis to explore design principles, strategies, and practices applicable to the region. The overview of rural dwellings in Inner Mongolia emphasizes geographical variation, ethnicity, ecological adaptability, use of local materials, architectural forms, spatial layout, and symbolic meanings. The proposed design principles prioritize respect for tradition, environmental sustainability, enhanced comfort and practicality, integration of modern technology, fostering regional interaction, and improving the tourism experience. Two case studies illustrate the pre-renovation analysis, design schemes, and effects of renovating a village residence in Tengke and a yurt tourism village in Tsarsen. The schemes involve preserving traditional features, adopting green technologies, adding modern facilities, and enhancing visitor experiences. Suggestions for operation and management include exploring operation modes, integrating tourism resources, promoting community participation, implementing effective marketing strategies, providing training programs, establishing supervision mechanisms, and conducting evaluations. The research acknowledges limitations and proposes future research directions, including further exploration of rural dwelling diversity, integration with other fields, practical exploration, sustainability considerations, and in-depth study of operation and management mechanisms.